2022
DOI: 10.4269/ajtmh.22-0164
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of the Remote Evaluation of Therapeutic Response in Cutaneous Leishmaniasis Using Photographs from a Mobile Application

Abstract: Cutaneous leishmaniasis (CL) primarily affects people in remote settings with limited access to health services. mHealth tools offer an opportunity to overcome knowledge gaps about clinical response to treatment. We evaluated the validity of the Guaral+ST mobile application for the remote assessment of therapeutic response in patients with CL, through photographs of lesions captured with the app by community health volunteers. Patients with confirmed CL were followed at weeks 13 and 26 after completion of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Another potential limitation is that the intervention arm was evaluated via photographs, while the control arm was evaluated in person. However, we have recently shown that evaluation by photographs is highly accurate [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential limitation is that the intervention arm was evaluated via photographs, while the control arm was evaluated in person. However, we have recently shown that evaluation by photographs is highly accurate [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has three main functions: i) promoting adherence to pharmacologic treatment, ii) measurement of adverse events associated with treatment, via periodic follow-up, and iii) assessment of therapeutic response via photographic evaluation. This evaluation strategy has been found to be sensitive and specific, relative to in-person assessment [ 12 ]. The intended users are community health volunteers and other healthcare workers.…”
Section: Methodsmentioning
confidence: 99%
“…Based on efficacy results of a previous study using the Guaral app for presumptive diagnosis and the Guaral+ST app by CHLs, 14 16 expert consensus, 29 , 30 and recommendations of the national guidelines, 6 a community-based strategy utilizing the Guaral+ST app was undertaken to monitor the treatment and follow the therapeutic response of CL patients.…”
Section: Methodsmentioning
confidence: 99%
“…The high accuracy of the remote evaluation of therapeutic response using the photographs taken with the app was previously demonstrated. 16 …”
Section: Introductionmentioning
confidence: 99%